Rumah Akses: Reconstructing Homes and Everyday Lives of the Newly Disabled Women after The 2006 Earthquake in Bantul, Yogyakarta - Fina Itriyati (Universitas Padjadjaran, 2020)
The 2006 earthquake in Yogyakarta had already passed. However, the process of adaptation carried out by every individual is different. In this article, I disclose the experiences of women with disabilities in their adaptation to their new lives, especially in building accessible homes, negotiating with donors and positioning themselves and their roles new in the family and community. By employing ethnographic methods, I found that even though women with disabilities experience limited mobility, marginalisation and stigma as passive recipients of assistance, they still try to build agencies while overcoming challenges during the process of housing reconstruction. To realise the accessible housing, they utilise their identity as persons with disabilities to complete their access houses, redefine the concept of an ideal home according to Javanese culture and maintain their position as a pillar of the household to maintain their bargaining power in the household. Through sabar (patience), nrimo (acceptance) and ikhlas (sincerity) women with new disabilities have exercised their agency not only in the process of housing reconstruction but also in the long-term journey of recovery after the disaster.